2019
DOI: 10.2169/internalmedicine.1528-18
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Acute Fulminant Eosinophilic Myocarditis in a Patient with Ulcerative Colitis Using Steroid Therapy and Percutaneous Cardiopulmonary Support

Abstract: A 47-year-old man with ulcerative colitis was transferred to our hospital due to progressive dyspnea. Electrocardiography on admission showed ST elevation in leads II, III, aVF, and V5-V6. Coronary angiography revealed no remarkable coronary stenosis, and left ventriculography showed a depressed left ventricular ejection fraction (EF) of 23%. Although the patient received percutaneous cardiopulmonary support, his EF progressively decreased (7-15%), and both ventricular tachycardia (VT) and high-degree atrial-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…This may partially explain the effects of glucocorticoids in treating autoimmune disease-induced FM. 27 Since the key pathological process of autoimmune disease-induced FM is self-antigen such as alpha or beta-MHC exposure to the immune system, it is convincing that disturbances of the immune system caused by autoimmune diseases lead to the formation of auto-cytotoxic immune cells, CD3 + / CD8 + T cell predominantly, as well as macrophages, targeting the myocardium, eventually leading to FM. 28 The third factor contributing to FM development is drug toxicity.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…This may partially explain the effects of glucocorticoids in treating autoimmune disease-induced FM. 27 Since the key pathological process of autoimmune disease-induced FM is self-antigen such as alpha or beta-MHC exposure to the immune system, it is convincing that disturbances of the immune system caused by autoimmune diseases lead to the formation of auto-cytotoxic immune cells, CD3 + / CD8 + T cell predominantly, as well as macrophages, targeting the myocardium, eventually leading to FM. 28 The third factor contributing to FM development is drug toxicity.…”
Section: Etiologymentioning
confidence: 99%
“… 56 , 57 In addition, lymphocyte myocarditis, eosinophilic myocarditis, and giant cell myocarditis are the result of significant immune disturbances. Degranulated eosinophils can be detected in the myocardium, suggesting key factors may be secreted affecting the local immune response, 27 , 50 however, the exact components involved remain unknown. Phenotypic differences in human leukocyte antigen (HLA) are reported to produce different immune responses triggered by the same stimulus, which suggests genetic variants might be related to different sensitivities to FM.…”
Section: Pathophysiological Mechanisms Underlying Fmmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Ang II, the first step in the activation process triggered by the binding to Ang II receptor is the mobilization of the Gα of the Gq protein, which activates the Rho-guanine exchange factors (RhoGEFs) to replace guanosine-50-diphosphate (GDP) with GTP. The GTP-Rho interaction with the RBD domain of Rho-Kinase leads to ROCK activation [ 39 ]. The activation of ROCK induces the activation of the NAD(P)H Oxidase, which is one of the most important enzymes responsible for superoxide ion production [ 40 ].…”
Section: Rho Kinase and Af: Molecular Mechanismsmentioning
confidence: 99%
“…The various complications of ulcerative colitis include arthritis and skin symptoms, and, in rare cases, can include eosinophilic disorders. Previous studies have reported eosinophilic esophagitis and myocarditis as complications of ulcerative colitis [ 1 , 2 ]. Eosinophilic pancreatitis (EP) is extremely rare among eosinophilic diseases, save for one report as a complication of ulcerative colitis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%